2015
DOI: 10.1002/j.0022-0337.2015.79.1.tb05862.x
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Shared Learning of Trainee Dental Technicians and Undergraduate Dental Students

Abstract: The challenges of health care are increasingly complex and subject to frequent change. Meeting these demands requires that health professionals work in partnership with each other and the patient. One way of contributing to this is for students to learn together. However, effective teamwork requires an education system that helps to foster understanding among all those entering the health workforce. The purpose of this study was to investigate the attitudes towards shared learning of undergraduate dental stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…7,12 It is suggested by Brooks and Gorman (2017) that IntraPE can cause role-blurring of professional identities between assumed roles and a hierarchy of responsibilities. Role-blurring has been perceived as positive or negative, 11 but the majority of current research supports early educational intervention of IntraPE or IPE to prevent silo identities, which can create persistent negative stereotypes toward other professionals. 3,[15][16][17] This can enhance care by sharing workloads among health professionals and allowing team members to learn new skills.…”
Section: Roles and Responsibilitiesmentioning
confidence: 96%
See 2 more Smart Citations
“…7,12 It is suggested by Brooks and Gorman (2017) that IntraPE can cause role-blurring of professional identities between assumed roles and a hierarchy of responsibilities. Role-blurring has been perceived as positive or negative, 11 but the majority of current research supports early educational intervention of IntraPE or IPE to prevent silo identities, which can create persistent negative stereotypes toward other professionals. 3,[15][16][17] This can enhance care by sharing workloads among health professionals and allowing team members to learn new skills.…”
Section: Roles and Responsibilitiesmentioning
confidence: 96%
“…The IntraPE curriculum in this study was primarily didactic with limited clinical interaction. Multiple studies between dental and DH students have shown participants desire more collaborative clinical time, 8,11 that clinical IntraPE is more effective than didactic learning, 2,6,13 and clinical IntraPE is the superior method to help students understand the roles and responsibilities of other health professionals. 6,24…”
Section: Roles and Responsibilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…23 An IPE event involving dental students and student doctors of nursing practice 24 found that students were respectful of each needs. Within the UK, dental students and student dental technicians linked together in the provision of dentures for a patient, resulted in the majority of students recognizing the benefits of shared learning and valuing the roles of team members, the acquisition of teamwork skills for their future careers and ultimately improving patient care 25 . Whilst general health profession IPE findings can be related to dentistry, further research in IPE within dentistry would be ideal in particular reporting outcomes in relation to patient care and service improvement.…”
Section: Effectiveness Of Interprofessional Educationmentioning
confidence: 99%
“…Previous studies have found that intraprofessional educational experiences improved teamwork within the dental profession, 8 facilitated a clearer understanding of each provider's roles and responsibilities within the health care team, 1 , 7 13 and improved patient outcomes 10 . Research in this area has focused on other allied dental professionals 1 , 9 , 12 or special projects with a short‐term shared learning experience between dental and dental hygiene students 8 . The aim of our study was to assess the perspectives of dental and dental hygiene students regarding collaborative learning after taking two courses together.…”
mentioning
confidence: 99%